2002
DOI: 10.1038/sj.pcan.4500569
|View full text |Cite
|
Sign up to set email alerts
|

Association between the GCG polymorphism of the selenium dependent GPX1 gene and the risk of young onset prostate cancer

Abstract: Epidemiological studies have suggested an association between low selenium levels and the development of prostate cancer. Human cellular glutathione peroxidase I (hGPX1) is a selenium-dependent enzyme that protects against oxidative damage and its peroxidase activity is a plausible mechanism for cancer prevention by selenium. The GPX1 gene has a GCG repeat polymorphism in exon 1, coding for a polyalanine tract of five to seven alanine residues. To test if the GPX1 GCG repeat polymorphism associates with the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 11 publications
1
22
1
Order By: Relevance
“…There have been few investigations of potential relationships between GPX1 genetic polymorphisms and prostate cancer risk, except for one study that assessed the GPX1 GCG repeat, finding no relationships with prostate cancer risk (29). In our study, we did not find an overall relationship between GPX1 Pro200Leu polymorphism and prostate cancer.…”
Section: Discussioncontrasting
confidence: 47%
“…There have been few investigations of potential relationships between GPX1 genetic polymorphisms and prostate cancer risk, except for one study that assessed the GPX1 GCG repeat, finding no relationships with prostate cancer risk (29). In our study, we did not find an overall relationship between GPX1 Pro200Leu polymorphism and prostate cancer.…”
Section: Discussioncontrasting
confidence: 47%
“…Perhaps the best candidate is GPx-1, because an association with polymorphisms and the risk of lung cancer has been reported, as has loss of heterozygosity at this locus in several cancer types (9)(10)(11)(12). In fact, an association between a polyalanine polymorphism in exon 1 and the risk of young-onset prostate cancer has been reported (28). Reduced levels of GPx-1 could conceivably influence cancer risk through its role as an antioxidant or possibly through the modulation of DNA repair and cell-survival molecules (15,29).…”
Section: Discussionmentioning
confidence: 99%
“…Although loss of heterozygosity at the GPx-1 locus has been associated with the development of several cancer types, including those occurring in lung, breast, and head and neck, no significant association between GPx-1 genotypes and CaP has been elucidated. Selenium, as a component of GPx, has been shown to play an important role in the manganese superoxide dismutase antioxidative pathway (14). A cohort study of Finnish male heavy smokers found that the manganese superoxide dismutase AA polymorphism was significantly associated with increased risk of CaP (15).…”
Section: Seleniummentioning
confidence: 99%